Adjuvant-induced arthritis in the temporomandibular joint of rats. - Zamma, T (1983)
When Lewis rats were immunized by intradermal injection into the parietal scalp rather than into the footpad with mycobacterial delipidated cells in squalene, arthritis could be produced in the temporomandibular joint (TMJ) with a maximum incidence of 60%, accompanied by systemic polyarthritis. Other methods of immunization including intradermal injection into the tail, posterior cervical region, or intra-inguinal lymph nodes did not induce arthritis in the TMJ. A combination of this inoculation and hemiocclusal loss markedly increased the incidence of arthritis in the TMJ. This arthritis in the TMJ was, however, milder than that in other joints and was apparent only histologically. The group given intradermal injection of adjuvants into the parietal scalp showed definite suppression of body weight gain. Since the method of intradermal injection into the parietal scalp can induce a high incidence of arthritis in the TMJ, our study presents a unique experimental model for study of arthritis in the TMJ.